2016
DOI: 10.3164/jcbn.15-71
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc supplementation increased TNFα and IL1β-induced RANKL expression, resulting in a decrease in bone mineral density in rats

Abstract: We investigated the effect of dietary zinc supplementation on bone metabolism in rats. Four-week-old male Wistar rats were fed a 30.0 mg zinc/kg diet (C), a 300.0 mg zinc/kg diet (HZ) or a 3,000.0 mg zinc/kg diet (EZ) for 4 weeks. The zinc content of the femur gradually increased in accordance with the gradual increase in the dietary zinc level. Although the mRNA expression of zinc transporters in bone did not differ between the groups, the mRNA expression of metallothioneins was increased in the HZ and EZ gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…4) The serum levels of osteocalcin and the C-terminal telopeptide of type I collagen (CTx) were measured as described previously. 8) Extraction of total RNA and synthesis of complementary DNA were performed as described previously. 8) For real-time PCR, the reaction mixture was prepared using the TaqMan Gene Expression Master Mix (Applied Biosystems, Foster, CA) with TaqMan gene expression assays (Applied Biosystems) for the following rat genes: Zip1, Zip13, Zip14, ZnT5, ZnT7, metallothionein (Mt)1a, Mt2A, bone morphogenetic protein 2 (BMP2), runt-related transcription factor 2 (Runx2), Osterix, alkaline phosphatase (ALP), Osteocalcin, Collagen typeⅠα 1(Col1a1), and β-actin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4) The serum levels of osteocalcin and the C-terminal telopeptide of type I collagen (CTx) were measured as described previously. 8) Extraction of total RNA and synthesis of complementary DNA were performed as described previously. 8) For real-time PCR, the reaction mixture was prepared using the TaqMan Gene Expression Master Mix (Applied Biosystems, Foster, CA) with TaqMan gene expression assays (Applied Biosystems) for the following rat genes: Zip1, Zip13, Zip14, ZnT5, ZnT7, metallothionein (Mt)1a, Mt2A, bone morphogenetic protein 2 (BMP2), runt-related transcription factor 2 (Runx2), Osterix, alkaline phosphatase (ALP), Osteocalcin, Collagen typeⅠα 1(Col1a1), and β-actin.…”
mentioning
confidence: 99%
“…Respective Assay IDs were described previously. 8,9) Gene transcript levels in each sample were determined using the relative standard curve method. The level of gene transcripts is expressed as a ratio relative to βactin mRNA, with the level in rats fed the control diet set to 1.…”
mentioning
confidence: 99%
“…Importantly, Zinc deficiency is associated with the excessive and tissue-damaging proinflammatory release of cytokines, including increased tumor necrosis factor-alpha (TNF-α) 33,34 and IL-6 35 .…”
Section: Zinc Deficiency Is Associated With Cytokine Stormmentioning
confidence: 99%
“…Notably, Zinc correction is associated with the down-regulation of tumor necrosis factor-alpha 30,33,34 .…”
Section: Zinc Deficiency Is Associated With Cytokine Stormmentioning
confidence: 99%
“…( 12 ) On the other hand, it is known that high phosphorus intake acutely and adversely affects bone metabolism in healthy young females. ( 15 ) Suzuki et al ( 16 ) reported that excessive intake of zinc leads to bone resorption and bone loss in rats.…”
Section: Introductionmentioning
confidence: 99%